Organic chemistry demystified - Bloch, Daniel R. , 1940- (Demystified series, 2012)
Overview: you don't need genius DNA to master organic chemistry! Whether you're taking a chemistry class or studying for the MCAT or DAT, Organic Chemistry Demystified is your formulas for learning or reviewing fundamental concepts and theories step-by-step. This practical guide eases you into this sometimes challenging subject, starting with atomic structure and mass. As you progress, you will master organic chemistry essentials such as the reactivity of functional groups, the three-dimensional structure of molecules, reaction mechanisms, and more. You will understand how compounds are named and how to predict reactions. Detailed examples make it easy to understand the material, and end-of-chapter quizzes and a final exam help reinforce key ideas. It's a no-brainer! You'll learn about: molecular orbitals and bonding. -- Acidic and basic properties of organic molecules. -- Structure and properties of functional groups. -- Characterization of molecules. -- Substitution and elimination reactions. -- Reaction mechanisms. -- Stereochemistry. -- Predicting reaction pathways. Simple enough for a beginner, but challenging enough for an advanced student, Organic Chemistry Demystified, second edition, helps you master this essential subject